Systemic nocardiosis in a dog caused by Nocardia cyriacigeorgica - Eroksuz, Yesari; Gursoy, Nafia Canan; Karapinar, Tolga; Karabulut, Burak; Incili, Canan Akdeniz; Yerlikaya, Zeynep; Eroksuz, Hatice (Biomed Central Ltd, 2017)
Background: Systemic nocardiosis due to Nocardia cyriacigeorgica has not been reported in dogs. Case presentation: Light and electron microscopy, microbiological culture and molecular identification (PCR) were used to diagnose systemic nocardiosis caused by Nocardia cyriacigeorgica in a 3-month-old husky dog. The postmortem changes included multifocal to coalescing, sharply circumscribed pyogranulomatous inflammation and abscess formation in lungs, liver, myocardium, spleen, kidneys, brain, and hilar lymph nodes. The organism was isolated and sequencing of its 16S rRNA allowed its identification and speciation. Examination of the bacterial culture by scanning electron-microscope showed filamentous branching with fragmentation into widely bacillary and cocoid forms of the bacteria. There was no history of immunosupressive drug administration and infection by the immunosuppresive viral pathogens, canine distemper and parvovirus were excluded via PCR. Conclusion: N. cyriacigeorgica should be considered potential cause of systemic pyogranulomatous lesions in dogs. It is the first reported case of systemic nocardiosis due to N. cyriacigeorgica in a dog.
Keywords: Canine nocardiosis; Nocardia cyriacigeorgica; Systemic involvement